2021
DOI: 10.1177/10732748211044355
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognosis of Squamous Cell Carcinoma of the Breast: A Population-Based Analysis

Abstract: Background To better understand the clinicopathological features and prognostic profiles of squamous cell carcinoma (SCC) of the breast. Methods Information on breast cancer was obtained from the Surveillance, Epidemiology, and End Results database (2004–2016). Comparative analyses were carried out to investigate the heterogeneity in the clinicopathological characteristics and survival outcomes between SCC and invasive ductal carcinoma (IDC), while propensity score matching was conducted to analyze the variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The inconsistent results regarding the above treatment methods indicate the need to examine more cases of ASCC. 19,20 Given the irreversible nature of the mass in the current case, we administered neoadjuvant therapy with albumin-paclitaxel, carboplatin, and trastuzumab, with excellent results, confirming the efficacy of this treatment for HER2-positive SCC. Postoperative pathology suggested that there was some residual carcinoma in situ in the lesion, ER and PR were highly expressed, and that the addition of anastrozole could reduce the risk of recurrence and metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…The inconsistent results regarding the above treatment methods indicate the need to examine more cases of ASCC. 19,20 Given the irreversible nature of the mass in the current case, we administered neoadjuvant therapy with albumin-paclitaxel, carboplatin, and trastuzumab, with excellent results, confirming the efficacy of this treatment for HER2-positive SCC. Postoperative pathology suggested that there was some residual carcinoma in situ in the lesion, ER and PR were highly expressed, and that the addition of anastrozole could reduce the risk of recurrence and metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…Central cystic degeneration is common in tumors larger than 2 cm, and this cavity is filled with necrotic squamous debris (4). Tumors with diffuse keratinization are macroscopically softer and granular in appearance (10).…”
Section: Discussionmentioning
confidence: 99%
“…Because it was reported in our patient who had an ulcerated skin lesion, the pathological examination revealed that the tumor had no cutaneous origin and developed primarily from the breast. When establishing a definitive diagnosis of primary squamous cell carcinoma of the breast, it may be possible after exclusion of metastasis from an extramammary primary squamous cell carcinoma, such as carcinomas of the lung, uterine cervix, bladder, and head and neck region (10). It is important to distinguish between Primary or Metastatic Squamous Cell Carcinoma because treatment protocols are very different.…”
Section: Discussionmentioning
confidence: 99%
“…Metaplastic carcinomas account for approximately 0.2—1% of all invasive breast cancers [ 1 ]. Squamous cell carcinoma (SCC) of the breast is a rare type of metaplastic cancer that accounts for approximately 0.1% of all invasive malignancies [ 2 ]. Owing to its extremely low prevalence, there is limited knowledge about its clinical presentation and lack of standardized treatment for SCC of the breast [ 3 ].…”
Section: Introductionmentioning
confidence: 99%